Supply Chain Processes : Developing Competitive Advantage through Supply Chain Process Excellence - Robertson, Peter W. (New York : Routledge, 2021)
"Supply Chain Processes introduces readers to the view that genuine supply chain competitive advantage is achieved via supply chain excellence which in turn is underpinned by supply chain process excellence. The ultimate supply chain goal is to deliver the right product, of the right quality, in the right quantity, to the right place, at the right time and for the right cost. The author identifies four core supply chain processes - strategy, design, execution and people - to which the process improvement techniques explained can be applied to ensure superior supply chain performance. Key topics are addressed, including supply chain risk, resilience, sustainability, challenges confronting modern-day supply chains and developing an elegant supply chain design. Each chapter starts with a section that explores learning opportunities and is followed by detailed chapter content. Carefully explained examples are provided, as well as end of chapter case studies, review questions and written assignments. A full suite of teaching aids is also provided for lecturers and tutors. Providing both management expertise and technical skills, which are essential to decision-makers in the supply chain, this textbook should be essential reading for undergraduate and post-graduate students, working people or mature aged persons wanting to upgrade their qualifications, and operating supply chain leaders and supply chain professionals. Online resources include chapter-by-chapter PowerPoint slides, tutorial exercises, written assignments and a test bank of exam questions"--
Includes bibliographical references and index.
Keywords: Business logistics; Competition